Dana Island : the greatest shipyard of the Ancient Mediterranean - Oniz, Hakan, (Archaeopress Archaeology, 2021)
This book presents the archaeological discoveries from Dana Island, off the coast of Rough Cilicia in southern Turkey, where underwater investigations and surface survey undertaken in advance of excavation revealed nearly 300 ancient rock-cut slipways, the largest number of such naval installations discovered to date.